2015
DOI: 10.1039/c5cp04050g
|View full text |Cite
|
Sign up to set email alerts
|

Imidazole tailored deep eutectic solvents for CO2 capture enhanced by hydrogen bonds

Abstract: Deep eutectic solvents (DESs) have emerged as promising alternative candidates for CO2 capture in recent years. In this work, several novel DESs were firstly prepared to enhance CO2 absorption. Structural and physical properties of DESs were investigated, as well as their absorption performance of CO2. A distinct depression in the melting point up to 80 K of DESs was observed compared with that of BMIMCl. The observed red shifts of the C2H group in an imidazolium ring and its chemical shifts downfield in NMR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
90
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(101 citation statements)
references
References 113 publications
(150 reference statements)
9
90
0
Order By: Relevance
“…Shukla et al reported that the CO 2 solubility in DES depends on the HB interactions between HBA and HBD (Shukla and Mikkola, 2018). Cao et al indicated that the formation of HB between HBA and HBD enhanced the CO 2 solubility in DESs (Cao et al, 2015). In addition, Atilhan et al investigated the interactions between DES and SO 2 by the quantum chemistry, confirming a dominant VdW interaction between DES and SO 2 (Atilhan et al, 2019).…”
Section: Excess Enthalpy Predictionmentioning
confidence: 99%
“…Shukla et al reported that the CO 2 solubility in DES depends on the HB interactions between HBA and HBD (Shukla and Mikkola, 2018). Cao et al indicated that the formation of HB between HBA and HBD enhanced the CO 2 solubility in DESs (Cao et al, 2015). In addition, Atilhan et al investigated the interactions between DES and SO 2 by the quantum chemistry, confirming a dominant VdW interaction between DES and SO 2 (Atilhan et al, 2019).…”
Section: Excess Enthalpy Predictionmentioning
confidence: 99%
“…[3] Moreover, treatment of the waste alkaline solution is an energy intensive process, which may causes econdary pollution to the environment. Recent progresses suggest that some green sorbents, for example, zeolites, [4] zeolitic imidazolate framework, [5][6][7][8] metal-organic framework, [9][10][11][12][13] ionic liquids, [14][15][16][17][18][19][20] base-containing, or porousp olymers, [21][22][23][24][25][26][27][28][29][30][31][32] carbonbased materials, [33,34] are very promising for CO 2 capturew ithout environmental pollution. However, the regeneration of these sorbents upon removing CO 2 has to involve endothermic processes,s till relying on the consumptiono ff ossil fuels.…”
mentioning
confidence: 99%
“…Traditional DESs are usually composed of hydrogen bond acceptor (HBA, e.g., quaternary ammonium salt or quaternary phosphonium salt) and hydrogen bond donor (HBD, e.g., organic acid or alcohol), where hydrogen bond between them makes the freezing points of the resultant DESs decrease greatly . Owing to the simple preparation as well as low cost and easy control, DESs have been increasingly applied to organic synthesis, electrochemistry, extraction separation, and gas absorption …”
Section: Introductionmentioning
confidence: 99%